Prenatal imaging of genital defects: clinical spectrum and predictive factors for severe forms. (18th March 2019) - Fuchs, Florent; Borrego, Paula; Amouroux, Cyril; Antoine, Benoît; Ollivier, Margot; Faure, Jean‐Michel; Lopez, Christophe; Forgues, Dominique; Faure, Alice; Merrot, Thierry; Boulot, Pierre; Jeandel, Claire; et al.
Abstract : Objectives: To report the clinical spectrum of genital defects diagnosed before birth, identify predictive factors for severe phenotypes at birth, and determine the rate of associated malformations. Patients and methods: A retrospective study (2008–2017) of 4580 fetuses, identified prenatally with abnormalities evaluated by our Reference Center for Fetal Medicine, included cases with fetal sonographic findings of abnormal genitalia or uncertainty of fetal sex determination. Familial, prenatal and postnatal data were collected via a standardised questionnaire. Results: In all, 61 fetuses were included. The positive predictive value (PPV) of the prenatal diagnosis of genital defects was 90.1%. Most cases were 46, XY‐undervirilized boys, 42 cases (68.8%), which included 29 with mid‐penile or posterior hypospadias, nine with anterior hypospadias, and epispadias, micropenis, scrotal transposition, and buried penis (one each). In all, 46, XX‐virilized girls were identified in seven cases (11.5%), which included four with congenital adrenal hyperplasia, two with isolated clitoromegaly, and one with ovotestis. Other defects included prune belly syndrome and persistent cloaca (six cases). Early detection during the second trimester (58.1% vs 18.8%, P  = 0.03), intra‐uterine growth restriction (IUGR) (45.2% vs 9.1%, P  = 0.06), and curvature of the penis (38.7% vs 0%, P  = 0.02), were more frequently related to severe defects in male newborns. Associated malformations (14 cases, 22.9%) and genetic defects (six) were frequent in undervirilized boys. Conclusion: Prenatal imaging of genital defects leads to a wide range of phenotypes at birth. Its PPV is high and extra‐urinary malformations are frequent. Early diagnosis during the second trimester, associated IUGR, and curvature of the genital tubercle, should raise suspicion of a severe phenotype and may justify delivery near a multidisciplinary disorders/differences of sex development team.